Combined Exposure to 33 Trace Elements and Associations With the Risk of Oral Cancer: A Large-Scale Case-Control Study - Wang, Huiying; Wang, Jing; Cao, Yujie; Chen, Jinfa; Deng, Qingrong; Chen, Yujia; Qiu, Yu; Lin, Lisong; Shi, Bin; Liu, Fengqiong; He, Baochang; Chen, Fa (Frontiers in Nutrition, 2022)
Background Trace elements exist widely in the natural environment and mostly enter the human body through drinking water or various types of food, which has raised increasing health concerns. Exposure to a single or a few trace elements has been previously reported to be associated with oral cancer risk, but studies on other elements and combined effects are limited. This study aimed to comprehensively evaluate the independent and joint effects of 33 trace elements on oral cancer risk. Methods The concentrations of 33 trace elements from the serum samples of 463 cases and 1,343 controls were measured using inductively coupled plasma mass spectrometry (ICP-MS). Propensity score matching was used to minimize the impact of potential confounders. Conditional logistic regression was utilized to evaluate the association of each element individually with oral cancer risk. Quantile g-computation and Bayesian kernel machine regression (BKMR) models were used to assess the joint effect of the overall element mixture and interactions. Results In single-element models, essential elements (Cu, Se, Zn, Sr, and Cr) and non-essential elements (As, Li, Th, Ce, Ti, and Sc) showed significant association with oral cancer risk. In multiple-element models, a quartile increase in overall non-essential elements was observed for a significant inverse association with oral cancer risk (β = −3.36, 95% CI: −4.22 to −2.51). The BKMR analysis revealed a potential beneficial joint effect of essential metals on the risk of oral cancer. Among these, higher levels of serum Zn and V exhibited an adverse effect, while serum Sr, Se, and Cu displayed favorable effects when all other essential elements were fixed at 25th or 50th percentiles. Of note, Se performed complex interactions among essential metals. As for non-essential elements, there were greater effect estimates for serum Th, Li, and Y when all other elements were held at the 75th percentile. Conclusion This study provides supportive evidence that the overall mixture effect of essential and non-essential elements might be associated with oral cancer risk, especially for serum Zn, V, Cu, Sr, Se, Th, Li, and Y. Extensive prospective studies and other experiments are warranted to confirm our findings.